Image and Accusations - Joshua Hardi Santoso (Institute of Research and Community Outreach - Petra Christian University, 2018)
Hoax news became more apparent in the recent time in Indonesia. This creative work would like to find out how the hoax destroys life and the struggle to restore. Later, I would like to show how the relationship, integrity and reputation destroyed by hoax and how the track records used to restore the reputation. The creative work follows a story of a victim of a slander whose life was destroyed by it and would like to repair his image back. He had to investigate the culprit behind the slander. He found out that the culprit was his own friend. He confronted the culprit to stop the slander once and for all. The held a press conference with the help of his friends to restore his reputation. This story is represented through realistic novel as this genre would create a sense of realism that the readers could relate to.